Estrategias de enfermería para promover el bienestar espiritual en los pacientes oncológicos - Mite Álvarez, Grace Christina (2025)
Introduction: Not only physical health is part of the impact of cancer on patients; emotional and spiritual health is also affected. However, the emphasis is placed on medical treatment and spiritual support, which is necessary for quality of life and to cope with the disease, is neglected. Objective: To analyze, through a review of the literature, the nursing strategies used for the promotion and improvement of spiritual well-being in cancer patients. Materials and methods: This is a systematic review of the literature on nursing interventions in the spiritual well-being of cancer patients. We conducted literature searches in Cochrane and PubMed using the PICO strategy. These studies include primary and systematic reviews published from 2019 to 2024. Results: A total of 21 articles were included in this study, revealing that the most representative nursing interventions with support for spiritual well-being in cancer patients are prayer, active listening, and emotional accompaniment. These strategies promote resilience, reduce anxiety, and deepen spiritual connection. However, practical implementation in clinical care is limited by insufficient resources and training. Conclusions: Spirituality plays an important role in cancer care, impacting the patient's resilience and hope. Strategies such as prayer and emotional accompaniment are used to strengthen their well-being.